Search for squeezed-pair correlations at RHIC - Padula, Sandra S. [UNESP]; Socolowski, O. [UNESP]; Csorgo, T.; Nagy, M. I. (Iop Publishing Ltd, 2008)
Squeezed correlations of particle-antiparticle pairs, also called back-to-back correlations (BBC), are predicted to appear if the hadron masses are modified in the hot and dense hadronic medium formed in high energy nucleus nucleus collisions. Although well established theoretically, the squeezed-particle correlations have not yet been searched for experimentally in high energy hadronic or heavy ion collisions, clearly requiring optimized forms to experimentally search for this effect. Within a non-relativistic treatment developed earlier we show that one promising way to search for the BBC signal is to look into the squeezed correlation function of pairs of phi's at RHIC energies, plotted in terms of the average momentum of the pair, K(12) = 1/2 (k(1) + k(2)). This variable's modulus, 2 vertical bar K(12)vertical bar, is the non-relativistic limit of the variable Q(bbc), introduced herewith. Some squeezing effects on the HBT correlation function are also discussed.